Mengembangkan Pola Pikir Positif untuk Memulai Wirausaha bagi Klien Binaan BNN Provinsi Jawa Barat - Pipin Sukandi; Neuneung Ratna Hayati; Rima Rahmayanti (Jurnal Abdimas Multidisiplin, 2022)
Purpose: Universities, one of the elements of society, can assist BNN in dealing with and eradicating narcotics crimes. One of the Tridharma of higher education, namely community service, can participate in activities to help BNN. One of the things our team is doing is assisting BNN in nurturing fostered clients who have been rehabilitated by BNN to become entrepreneurs so as not to fall back into a dark world. Method: This method is carried out online for BNN-assisted clients by starting to develop a positive mindset that although former drug addicts they can be successful with one of them is to create jobs for themselves and the surrounding community. Result: The result will be continuous training for these BNN mentors and in the future it is hoped that there will be mentoring for those who open entrepreneurs. Limitation: The limitations of this activity are in terms of time and cost so that it can only be carried out for the West Java Province BNN in the meantime.